Morfologia, germinação e conservação in vitro de grãos de pólen de jenipapeiro - Freire, Gilmara da Silva (2025)
Genipa americana L. is a native species, but not endemic to Brazil, and is considered a fruit tree of economic interest. However, despite its importance, there is a lack of studies on its floral biology and other areas of interest. This work was divided into five chapters. The first evaluated the viability of pollen grains of the Siriri accession at room temperature in different culture media. The number of germinated pollen grains was analyzed at 24-hour intervals, up to 288 hours after incubation. The culture medium with 100 mg L-1 of H3BO3, 80 g L-1 of sucrose and 1.0 g L-1 of agar results in a higher to intermediate germination percentage, being the most suitable for studies of pollen viability of genipap. In the second chapter, the storage of pollen grains under different conditions was tested. The flowers were collected at the Siriri accession, and after extraction, the pollen grains were kept in cryovials at the following temperatures: 4°C, -20°C, -80°C and -196°C. Evaluations were performed at 30, 60, 90, 120, 150 and 180 days. After 180 days, the pollen germination percentages were higher than 60% for all temperatures. The lowest percentage was observed at a temperature of 4°C, with 60.21%. The other temperatures are more suitable for ex situ conservation of pollen grains. The third chapter evaluated the in vitro pollen viability in genipap accessions (AR2, AR4, CA and CR3) at room temperature in different culture media and through acetic carmine dye. The highest viability was obtained by accession CR3 in Lora medium for 96h of incubation (86.56%). Regarding viability by acetic carmine dye, there was no significant difference in the viability time for accessions AR2 and CR3. Lora medium is superior for viability studies by in vitro germination of pollen grains in genipap accessions. The fourth chapter analyzed the effect of low and ultra-low temperatures (4°C, -20°C, -80°C and -196°C) and storage time on the in vitro germination of pollen grains of genipap accessions (AR2, CR5, CA and MS). The CA and CR5 accessions showed a quadratic response as a function of storage time, with the highest estimated germination viability of 91.51 and 97.58%, at 95.23 and 117.3 days of conservation, respectively; the MS and AR2 accessions did not show regression adjustment. Considering the storage time and temperature, at 90 and 120 days, all conditions provided high viability, greater than 84%. Histological analysis at room temperature and under different storage conditions did not reveal changes in cellular structural characteristics. The fifth chapter characterized the pollen morphology and identified the pollen grains of the genipap tree (accessions AR2, CR5, MS and CA) using the acetolysis method. The pollen grains are 3-colporate, with reticulate to microreticulate ornamentation. They are considered small to medium in size, and have an oblate-spheroidal shape, with a small polar area. The characteristics presented confirm the variation within the species, that is, they are eurypollyn.